Improved harmonic injection pulse‐width modulation variable frequency triangular carrier scheme for multilevel inverters. Issue 14 (1st November 2020) - Orfi Yeganeh, Mohammad Sadegh; Sarvi, Mohammad; Blaabjerg, Frede; Davari, Pooya
Abstract : This study proposes an optimised controllable pulse‐width modulation (PWM) scheme suitable for multilevel inverters. Seeing the need for improving the output voltage characteristics such as total harmonic distortion, low‐order harmonic and distortion factor, an improved harmonic injection PWM variable frequency triangular carrier modulation technique is employed for off‐line mode. For this purpose, the carrier signal frequencies at each level (carrier‐based), and also amplitudes and orders of the harmonic‐injected signal (reference‐based) are considered as controllable parameters. The proposed technique benefits are operating with considerably fewer numbers of the pulses per cycle, low switching losses, and improvement in the output voltage characteristics. However, selective harmonic elimination and optimal switching angles are the most common modulation techniques, but they employ only one angle as a control parameter at each level of the output waveform. Hence, the modulation scheme can consider more angles at each level as controllable parameters by applying multi‐objective particle swarm optimisation and non‐dominated sorting genetic algorithm II (NSGA‐II). Simulations are conducted in 5‐, 7‐ and 9‐level inverter. Finally, the effectiveness of the studies is validated by obtaining experimental results on a single‐phase 1 kW 7‐level inverter prototype.